Diagnostic performance of serum calprotectin in discriminating active from inactive ulcerative colitis in an outpatient setting. (November 2022) - Udegbune, Michael; Sharrod–Cole, Hayley; Townsend, Sarah; Allen, Ben; Brookes, Matthew J; Ford, Clare; Gama, Rousseau
There are limited and conflicting data on the value of serum calprotectin (sCp) in discriminating active from inactive disease activity in ulcerative colitis (UC). Faecal calprotectin (fCp), sCp, serum C-reactive protein (sCRP) and platelets were compared in patients with UC who had clinically active (n = 29) and clinically inactive (n = 42) disease. Serum calprotectin was measured with Bühlmann ® (BMN sCp) and Immunodiagnostik TM (IDK sCp) assays. Median (interquartile range) fCp was higher in active than inactive disease [1004 (466–1922) versus 151 (55–280) µg/g; p < 0.0001). BMN sCp [4534 (3387–6416) versus 4031 (2401–5414) ng/mL; p = 0.1825], IDK sCp [4531 (2920–6433) versus 3307 (2104–4789) ng/mL; p = 0.1065], sCRP [ 4 (2–8) versus 2 (1–4) mg/L; p = 0.0638) and platelets [269 (233–331) versus 280 (227–325) ×10 −9 /L; p = 0.8055] were similar in active and inactive disease respectively. The area under the receiver operator characteristics curves with 95% confidence limits were 0.85 (0.76–0.94) for fCp, 0.61 (0.47–0.74) for BMN sCp, 0.61 (0.48–0.75) for IDK sCp, 0.69 (0.56–0.81) for sCRP and 0.52 (0.38–0.66) for blood platelets. Faecal calprotectin is the optimum biomarker for discriminating between active and inactive UC. The diagnostic performance of sCp, irrespective of assay, and systemic biomarkers was poor; of these sCRP performed best.